A comparative study of electrodes in the direct synthesis of CH4 from CO2 and H2O in molten salts. (20th July 2017) - Ji, Deqiang; Liu, Yue; Li, Zhida; Yuan, Dandan; Yang, Guanjian; Jiang, Mengpei; Wang, Yuhang; Yu, Yanyan; Wu, Hongjun
Abstract: Since the Industrial Revolution, the heavy reliance on the limited fossil energy has emitted huge number of CO2 into the air and led to a severely global warming. We propose a new green technology to moderate greenhouse gas CO2 emission and transform it into low-carbon renewable energy in this paper. Through this manner, electricity is transformed into chemical energy. CO2 and H2 O is directly simultaneous electrolysis under constant 0.25 A with 30 cm 2 nickel anode and 30 cm 2 iron cathode in a 600 °C alkali carbonate with LiOH electrolyte in mole ratio of nH :nC  = 0.15:1, achieving the storage of electricity to chemical energy. This electrolysis provides a gaseous product comprising 45.9% methane, 53.1% H2, 0.92% CO and trace amounts of longer (than methane) hydrocarbons. Simultaneously, the current efficiency is still ∼51% for 60 min. Highlights: A green technology to transform CO2 /H2 O into low-carbon energy is proposed. Methane can be obtained in only one-step without Fischer–Tropsch synthesis. Electrolyte can regenerate to the original state with supplement of CO2 /H2 O. The Ni anode and Fe cathode are comparatively stable after electrolysis.